The Complexities and Benefits of Community-Partnered Projects for Engineering Capstone Design Students - Marissa H. Forbes; Gordon D. Hoople (Trends in Higher Education, 2023)
Community-partnered engineering projects provide a mechanism for cultivating the development of sociotechnical engineers prepared to design within diverse and complex cultural, environmental, social, and other contexts. During the 2021–2022 academic year, we guided three teams of senior undergraduate engineering students through year-long community-partnered projects for their required capstone design course, which instead typically features corporate/industry-sponsored projects. We analyzed end-of-semester reflections (both fall and spring semester) from each student using inductive thematic analysis to explore how they perceived their experiences. The themes that emerged from the student reflections, including connectivity, transdisciplinary, multiple stakeholders, sustainability, justice, and ethics, are all components of the sociotechnical engineering capabilities that we are working to develop in our students. We consider these findings encouraging, and suggestive that integrating community-partnered projects into engineering capstone design offerings is worthwhile and effective. However, our implementation was not without challenges, such as trying to force the projects to fit into a course structure and timeline developed to support corporate/industry-sponsored project teams, which was burdensome to the community-partnered project teams. In this paper, we highlight both the complexities and benefits of this approach and insights gained from student and instructor reflections.